RETRACTED: Pathophysiological aspects of phospholipid metabolism in rats exposed to acute hypoxia of different etiologies - Kanaeva Elena; Pavlova Olga; Gulenko Olga; Bukareva Olga; Moskvitina Polina; Khan Azizuddin (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001